2001
DOI: 10.1111/j.1151-2916.2001.tb00730.x
|View full text |Cite
|
Sign up to set email alerts
|

Seamless Joining of Silicon Nitride Ceramics

Abstract: High-strength joining of Si 3 N 4 ceramics has been achieved by developing a process that effectively eliminates the seam, and may allow for fabrication of large or complex silicon nitride bodies. This approach to joining is based on the concept that when sintering aids are effective in bonding individual grains, they could be equally effective in joining bulk pieces of Si 3 N 4 . Optimization of the process led to Si 3 N 4 /Si 3 N 4 joints with room-temperature bend strengths as high as 950 MPa, corresponding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…5) Most silicon nitrides joined by glass with no or low pressure (<0.01 MPa) exhibited strengths in the range 400600 MPa, 9),11),12) whereas silicon nitride joined by glass under optimized conditions had a strength of over 900 MPa. 13) Therefore, the strength obtained in this study (446 MPa) is comparable to the moderate results previously reported. Therefore, microwave local heating can achieve a joint strength comparable to those obtained by conventional resistance furnace heating.…”
Section: Microstructure and Strength Of Joined Silicon Nitridesupporting
confidence: 90%
“…5) Most silicon nitrides joined by glass with no or low pressure (<0.01 MPa) exhibited strengths in the range 400600 MPa, 9),11),12) whereas silicon nitride joined by glass under optimized conditions had a strength of over 900 MPa. 13) Therefore, the strength obtained in this study (446 MPa) is comparable to the moderate results previously reported. Therefore, microwave local heating can achieve a joint strength comparable to those obtained by conventional resistance furnace heating.…”
Section: Microstructure and Strength Of Joined Silicon Nitridesupporting
confidence: 90%
“…6) A glass composed of the 2Re 2 O 3 SiO 2 (Re 2 O 3 = Y 2 O 3 , Yb 2 O 3 ) system was used as an insert, and joining was performed. Although a high strength was achieved under optimized joining temperatures and time, the glass remained at the joined interface.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the bonding of ceramics with oxide or oxynitride glass adhesives has been successful [14][15][16][17]. Since the sintering aids contribute to excellent bonding between Si 3 N 4 grains during the synthesis process, they should also be applicable for the joining of bulk materials.…”
Section: Introductionmentioning
confidence: 99%